Access to safe water and personal hygiene practices in the Kulandia Refugee Camp (Jerusalem) - Mohamad Issa; Michael McHenry; Abdul Aziz Issa; R. Alexander Blackwood (MDPI AG, 2015)
Diarrheal illness, frequently associated with fecal-oral transmission, is one of the leading causes of death worldwide. It is commonly preventable through the implementation of safe water practices. This experiment concerns how to best implement safe water practices in a quasi-permanent refugee camp setting with limited ability for structural changes. Specifically, we explore how health promotion activities that help identify target groups for hygiene interventions can play a role in disease prevention. An anonymous survey was conducted at the United Nations Relief and Works Agency Health Clinic in the Kulandia refugee camp to assess the safe water and personal hygiene practices. Demographic and social characteristics, accessible water and personal hygiene characteristics, and gastrointestinal (GI) burden for individuals and their households were assessed. A total of 96 individuals were enrolled; 62 females and 34 males. Approximately 58% of the sample had soap available and washed hands before and after eating and when preparing food. Piped water was the main source of drinking water (62%), while 31% of our sample utilized tanker-trucks. 93% of participants had access to toilet facilities, with 86% of these facilities being private households. 55% practice extra water hygiene measures on their household drinking water source. 51.3% considered vendor cleanliness when they were buying food. 51% had received formal health education. 68.8% had been taught by their parents, but only 55.2% were teaching their children and 15.6% had consistent access to a health professional for hygiene inquiries. Individual variables and hygiene practices associated with lower rates of diarrheal illnesses included having water piped into the home, proper hand washing, adequate soap availability, proper consideration of vendor cleanliness, higher income, levels of education, health hygiene education, and having access to healthcare professions to discuss hygiene related matters. This is the first study to assess the water and personal hygiene practices at the Kulandia refugee ramp. This study demonstrates that hygiene education and better practices are closely associated with the rate at which individuals and households suffer from diarrheal illnesses within the Kulandia refugee camp. There are significant hygiene deficits in the camp, which likely result from a lack of formal hygiene education and a lack of awareness concerning the connection between diarrheal illness and hygiene. With respect to practices, our results elucidate several areas where basic, communal programming - including lessons on appropriate hand washing and food preparation - will likely improve hygiene practices and decrease overall GI burden.